Preparation method of fuel cell membrane electrode
By introducing metal organic framework nanomaterials into the anode catalytic layer of the fuel cell membrane electrode, the problems of low conductivity and poor compatibility of the existing membrane electrode are solved, and more efficient self-humidifying performance and electrochemical performance are achieved.
Patent Information
- Application Number
- CN202411657161.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-01-24
AI Technical Summary
The existing fuel cell membrane electrode self-humidification design additives have low conductivity and poor compatibility, resulting in a decrease in electrochemical performance of membrane electrodes.
By mixing catalysts, vertical, decentralized solvents, deodorizing water, and metal organic frame nanomaterials in accordance with specific quality, prepare anode and catalytic catalytic slurry, and apply it to the proton exchange membrane to form a self -to -form self. Dipidial membrane electrode.
This method improves the self-humidifying performance and electrochemical performance of the membrane electrode by introducing metal-organic framework nanomaterials into the anode catalytic layer, reduces the internal resistance of the battery, and improves compatibility with perfluorosulfonic acid ion-based polymers. sex.
Smart Images

Figure CN119361724A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fuel cells, and in particular to a method for preparing a fuel cell membrane electrode. Background Art
[0002] Proton exchange membrane fuel cells are new energy batteries with high proton conductivity, environmental friendliness, and rapid start-up at room temperature. The proton exchange membranes used in commercial fuel cell vehicles are usually perfluorosulfonic acid ion-based polymer membranes, which are characterized by high mechanical and chemical stability. However, the proton transport capacity of polymer membranes represented by polyperfluorosulfonic acid is heavily dependent on their degree of hydration. Usually, in fuel cell stack systems, additional humidification systems and strict water management are required to ensure the water content in ion polymers, but this undoubtedly increases the volume and cost of the system.
[0003] Currently, developers add hydrophilic inorganic particles or polymers to the proton exchange membrane, catalyst layer or gas diffusion layer to enhance the humidification and water retention capacity of the catalyst-loaded proton membrane. However, the above substances usually have low conductivity, increase the internal resistance of the battery, and are difficult to distribute evenly, which ultimately leads to a decrease in the electrochemical performance of the membrane electrode. Summary of the invention
[0004] In view of the above problems, the present invention is proposed to provide a method for preparing a fuel cell membrane electrode, aiming to solve the problems of low conductivity and poor compatibility of additives in existing membrane electrode self-humidification designs.
[0005] According to a first aspect of the present invention, there is provided a method for preparing a fuel cell membrane electrode, comprising:
[0006] The catalyst, ionomer, dispersion solvent, deionized water and metal organic framework nanomaterial are uniformly mixed in a mass ratio of 1: (0.1-0.8): (50-250): (35-150): (0.001-0.08) to obtain an anode catalyst layer slurry;
[0007] The catalyst, ionomer, dispersion solvent and deionized water are uniformly mixed in a mass ratio of 1: (0.1-0.8): (50-250): (35-150) to obtain a cathode catalyst layer slurry;
[0008] The anode catalyst layer slurry is coated on the anode side of the proton exchange membrane to obtain an anode catalyst layer; the cathode catalyst layer slurry is coated on the cathode side of the proton exchange membrane to obtain a cathode catalyst layer;
[0009] The anode catalyst layer and the cathode catalyst layer are used as catalyst layers of a membrane electrode to prepare a self-humidifying membrane electrode.
[0010] Optionally, the proton exchange membrane is one of Nafion211, Nafion212, HP, XL100, NC700, and Gore.
[0011] Optionally, the catalyst includes a platinum-carbon catalyst and / or a platinum alloy catalyst; the dispersing solvent is any one of ethanol, n-propanol, and isopropanol.
[0012] Optionally, the platinum loading of the cathode catalyst layer is 0.20-0.40 mg / cm 2 The platinum loading of the anode catalyst layer is 0.02-0.10 mg / cm 2 .
[0013] Optionally, the metal organic framework nanomaterial is a sulfonated zirconium-based metal organic framework nanoparticle.
[0014] Optionally, the process of preparing the sulfonated zirconium-based metal organic framework nanoparticles comprises:
[0015] Using zirconium chloride as a zirconium source;
[0016] Using terephthalic acid and aminoterephthalic acid as ligands;
[0017] Using 2,5-diaminoterephthalic acid and N,N-dimethylformamide as solvents;
[0018] The ligand, the solvent and the zirconium source are uniformly mixed by ultrasonication, placed in a high-temperature reactor at 120 degrees for 20 hours, and washed and dried with ethanol to obtain a mixed substance;
[0019] 1-ethyl-(3-dimethylaminopropyl)carbodiimide, N-hydroxysulfosuccinimide and the mixed substance are added into the sulfoacetic acid solution, and then washed and dried after being immersed for 24 hours to obtain sulfonic acid group-modified zirconium-based metal organic framework nanoparticles.
[0020] Optionally, the zirconium-based metal organic framework nanoparticles are one of UiO-66(Zr), UiO-66(Zr)-NH2, and UiO-66(Zr)-(NH2)2.
[0021] The above one or more technical solutions in the embodiments of this specification have at least the following technical effects:
[0022] The present specification provides a method for preparing a fuel cell membrane electrode, wherein the catalyst, ionomer, dispersion solvent, deionized water and metal organic framework nanomaterial are mixed in a mass ratio of 1: (0.1-0.8): (50-250): (35-150): (0.001-0.08) to obtain an anode catalyst layer slurry; the catalyst, ionomer, dispersion solvent and deionized water are mixed in a mass ratio of 1: (0.1-0.8): (50-250): (35-150) to obtain a cathode catalyst layer slurry; the anode catalyst layer slurry is coated on the anode side of the proton exchange membrane to obtain an anode catalyst layer; the cathode catalyst layer slurry is coated on the cathode side of the proton exchange membrane to obtain a cathode catalyst layer; the anode catalyst layer and the cathode catalyst layer are used as catalyst layers of the membrane electrode to prepare a self-humidifying membrane electrode. In this way, by introducing the metal organic framework nanomaterial into the anode catalyst layer, the self-humidifying performance of the anode catalyst layer is designed. This nanomaterial has a unique large specific surface area, high porosity, high electron mobility, good thermal stability and chemical stability, and can also promote the conduction of hydrogen protons.
[0023] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Also, throughout the accompanying drawings, the same reference figures are used to represent the same components. In the drawings:
[0025] Figure 1 A flow chart showing a method for preparing a fuel cell membrane electrode in an embodiment of the present invention is shown.
[0026] Figure 2 A schematic diagram of a membrane electrode structure in an embodiment of the present invention is shown.
[0027] Figure 3 A schematic diagram of a performance test in an embodiment of the present invention is shown.
[0028] Figure 4 A schematic diagram of a performance test in a comparative example of the present invention is shown. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.
[0030] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.
[0032] In the description of the present invention, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "connect" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0033] The present invention provides a method for preparing a fuel cell membrane electrode. Figure 1 , Figure 2 As shown, the method for preparing the fuel cell membrane electrode comprises steps 101 to 104:
[0034] Step 101: uniformly mixing the catalyst, ionomer, dispersing solvent, deionized water and metal organic framework nanomaterial according to a mass ratio of 1: (0.1-0.8): (50-250): (35-150): (0.001-0.08) to obtain an anode catalyst layer slurry;
[0035] In this embodiment, the catalyst includes a platinum-carbon catalyst and / or a platinum alloy catalyst. The dispersion solvent may be any one of ethanol, n-propanol, and isopropanol. Deionized water refers to pure water from which impurities in the form of ions have been removed.
[0036] After the catalyst and the dispersion solvent are determined, the catalyst, ionomer, dispersion solvent, deionized water and metal organic framework nanomaterial are uniformly mixed in a mass ratio of 1: (0.1-0.8): (50-250): (35-150): (0.001-0.08) to obtain an anode catalyst layer slurry.
[0037] The metal organic framework nanomaterial may be sulfonated zirconium-based metal organic framework nanoparticles.
[0038] The zirconium-based metal organic framework nanoparticles can be any one of U iO-66(Zr), U iO-66(Zr)-NH2, and U iO-66(Zr)-(NH2)2.
[0039] The process of preparing the sulfonated zirconium-based metal organic framework nanoparticles comprises:
[0040] Using zirconium chloride as a zirconium source;
[0041] Using terephthalic acid and aminoterephthalic acid as ligands;
[0042] Using 2,5-diaminoterephthalic acid and N,N-dimethylformamide as solvents;
[0043] The ligand, the solvent and the zirconium source are uniformly mixed by ultrasonication, placed in a high-temperature reactor at 120 degrees for 20 hours, and washed and dried with ethanol to obtain a mixed substance;
[0044] 1-ethyl-(3-dimethylaminopropyl)carbodiimide, N-hydroxysulfosuccinimide and the mixed substance are added into the sulfoacetic acid solution, and then washed and dried after being immersed for 24 hours to obtain sulfonic acid group-modified zirconium-based metal organic framework nanoparticles.
[0045] It should be noted that the metal organic framework nanomaterial can also be selected from any one of MOF-5, ZIF-8, ZIF-67, MOF-199, UiO-66 and MIL-53. After sulfonation treatment, the same membrane electrode self-humidification effect can be achieved by adding an anode catalyst layer.
[0046] Step 102: uniformly mixing the catalyst, ionomer, dispersing solvent and deionized water in a mass ratio of 1: (0.1-0.8): (50-250): (35-150) to obtain a cathode catalyst layer slurry;
[0047] In this embodiment, the catalyst includes a platinum-carbon catalyst and / or a platinum alloy catalyst. The dispersion solvent may be any one of ethanol, n-propanol, and isopropanol. Deionized water refers to pure water from which impurities in the form of ions have been removed.
[0048] After the catalyst and the dispersion solvent are determined, the catalyst, ionomer, dispersion solvent and deionized water are uniformly mixed in a mass ratio of 1: (0.1-0.8): (50-250): (35-150) to obtain a cathode catalyst layer slurry.
[0049] Step 103: coating the anode catalyst layer slurry on the anode side of the proton exchange membrane to obtain an anode catalyst layer; coating the cathode catalyst layer slurry on the cathode side of the proton exchange membrane to obtain a cathode catalyst layer;
[0050] In this embodiment, the proton exchange membrane is one of Nafion 211, Nafion 212, HP, XL100, NC700, and Gore. The anode side and the cathode side of the proton exchange membrane are arranged opposite to each other and are used to coat the anode catalyst layer slurry and the cathode catalyst layer slurry.
[0051] Among them, the platinum loading of the cathode catalyst layer is 0.20-0.40 mg / cm 2 The platinum loading of the anode catalyst layer is 0.02-0.10 mg / cm 2 .
[0052] Step 104: using the anode catalyst layer and the cathode catalyst layer as catalyst layers of a membrane electrode to prepare a self-humidifying membrane electrode.
[0053] Example:
[0054] 0.1g zirconium chloride and 0.08g aminoterephthalic acid were dissolved in 20mL N,N-dimethylformamide, ultrasonically mixed and placed in a high-temperature reactor at 120 degrees for 20 hours, then washed and dried with ethanol; then 1-ethyl-(3-dimethylaminopropyl)carbodiimide, N-hydroxysulfosuccinimide, and the above substances were added to the sulfoacetic acid solution, soaked for 24 hours, washed and dried, and sulfonic acid group-modified U i O-66(Zr)-NH2 particles were obtained.
[0055] 0.2 g of a platinum-carbon catalyst having a platinum content of 50%, 4 g of deionized water, 80 mg of an ionomer (the concentration of the ionomer solution is 10%), 18 g of isopropanol / ethanol (2:1) and 0.007 g of U iO-66(Zr)-NH 2 particles were mixed and ultrasonically dispersed to prepare a cathode catalyst layer slurry;
[0056] Mix 0.2 g of a platinum-carbon catalyst having a platinum content of 50%, 4 g of deionized water, 80 mg of an ionomer (the concentration of the ionomer solution is 10%), and 18 g of isopropanol / ethanol (2:1), and prepare a cathode catalyst layer slurry after ultrasonic dispersion;
[0057] A cathode catalyst layer was coated on a Gore 15 micron proton membrane at 80 degrees using an ultrasonic sprayer, and then an anode catalyst layer was coated on the anode layer of the proton membrane to prepare a fuel cell membrane electrode with self-humidification performance.
[0058] Comparison example:
[0059] The difference between the comparative example and the aforementioned embodiment is that no metal organic framework nanomaterial is added to the anode catalyst layer, and other parameters and conditions are exactly the same as those in the embodiment.
[0060] Performance Test:
[0061] Combination Figure 3 , Figure 4 As shown, carbon paper was placed on both sides of the membrane electrode described in the embodiment and the comparative example to assemble a single cell, and the activation area was 25 cm 2 The test was carried out under the conditions of battery temperature of 80 degrees, gas excess coefficient H2 / Ai r=1.5 / 2.5 and no back pressure.
[0062] Under different cathode humidity conditions, compared with the data of the comparative example, it can be seen that the self-humidification effect of the embodiment is significant, and the performance of the membrane electrode is significantly improved under low humidity conditions.
[0063] In summary, the method for preparing a fuel cell membrane electrode provided in the embodiments of this specification is designed by designing the self-humidifying performance of the anode catalyst layer, specifically, introducing a metal organic framework nanomaterial into the anode catalyst layer. This nanomaterial has a unique large specific surface area, high porosity, high electron mobility, good thermal stability and chemical stability. This material can also promote the conduction of hydrogen protons. In addition, by sulfonating the material, the compatibility with the perfluorosulfonic acid ion-based polymer is improved, so that it is evenly dispersed in the catalyst layer.
[0064] After sulfonation of the metal organic framework nanomaterials, the hydrophilicity is further improved, which weakens the hydrophobicity of the anode catalyst layer and has the effect of retaining water and absorbing moisture. When the battery is running, hydrogen protons carry a certain number of water molecules from the anode to the cathode for electropermeation. As the current density increases, the electropermeation rate increases, resulting in water shortage at the anode and increased membrane internal resistance, while water accumulation at the cathode will cause flooding. After the wettability of the anode catalyst layer changes, driven by the concentration gradient, water molecules are more likely to diffuse from the cathode catalyst layer to the anode catalyst layer, thereby wetting the anode catalyst layer and the proton exchange membrane. Therefore, the membrane electrode has a self-humidification function, and the metal organic framework nanomaterial itself has a high electron migration rate and will not increase the battery impedance.
[0065] The above are only various embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a fuel cell membrane electrode, characterized in that: include: The catalyst, ionomer, dispersion solvent, deionized water and metal organic framework nanomaterial are uniformly mixed in a mass ratio of 1: (0.1-0.8): (50-250): (35-150): (0.001-0.08) to obtain an anode catalyst layer slurry; The catalyst, ionomer, dispersion solvent and deionized water are uniformly mixed in a mass ratio of 1: (0.1-0.8): (50-250): (35-150) to obtain a cathode catalyst layer slurry; The anode catalyst layer slurry is coated on the anode side of the proton exchange membrane to obtain an anode catalyst layer; the cathode catalyst layer slurry is coated on the cathode side of the proton exchange membrane to obtain a cathode catalyst layer; The anode catalyst layer and the cathode catalyst layer are used as catalyst layers of a membrane electrode to prepare a self-humidifying membrane electrode.
2. The method according to claim 1, characterized in that The proton exchange membrane is one of Nafion211, Nafion212, HP, XL100, NC700 and Gore.
3. The method according to claim 1, characterized in that The catalyst includes a platinum-carbon catalyst and / or a platinum alloy catalyst; the dispersion solvent is any one of ethanol, n-propanol and isopropanol.
4. The method according to claim 3, characterized in that The platinum loading of the cathode catalyst layer is 0.20-0.40 mg / cm2; the platinum loading of the anode catalyst layer is 0.02-0.10 mg / cm2.
5. The method according to claim 1, characterized in that The metal organic framework nano material is sulfonated zirconium-based metal organic framework nano particles.
6. The method according to claim 5, characterized in that The process of preparing the sulfonated zirconium-based metal organic framework nanoparticles comprises: Using zirconium chloride as a zirconium source; Using terephthalic acid and aminoterephthalic acid as ligands; Using 2,5-diaminoterephthalic acid and N,N-dimethylformamide as solvents; The ligand, the solvent and the zirconium source are uniformly mixed by ultrasonication, placed in a high-temperature reactor at 120 degrees for 20 hours, and washed and dried with ethanol to obtain a mixed substance; 1-ethyl-(3-dimethylaminopropyl)carbodiimide, N-hydroxysulfosuccinimide and the mixed substance are added into the sulfoacetic acid solution, and then washed and dried after being immersed for 24 hours to obtain sulfonic acid group-modified zirconium-based metal organic framework nanoparticles.
7. The method according to claim 5 or 6, characterized in that: The zirconium-based metal organic framework nanoparticles are one of UiO-66(Zr), UiO-66(Zr)-NH2, and UiO-66(Zr)-(NH2)2.